Network Capability, Knowledge Creation, Product Innovation, and Marketing Performance of Micro, Small, and Medium Enterprises (MSMEs) - Eko Sasono; Wanuri Wanuri; Siti Khayatun (Management Analysis Journal, 2023)
Micro, Small, and Medium Enterprises (MSMEs) are one of the most developed creative industries in Indonesia and are able to make significant contribution to Indonesia's GDP (Gross Domestic Product), but the high growth of MSMEs has not been able to create sustainable MSMEs performance. Factors that influence each other include network capability, marketing performance, knowledge creation, and product innovation. This study aims to empirically prove the effect of network creation on marketing performance and knowledge creation, the effect of knowledge creation on product innovation, and the effect of product innovation on marketing performance. The sample in this study were 250 respondents of MSME owners in Semarang City. The data collection method used questionnaire distributed to MSMEs owners through Google Forms. Data analysis used descriptive statistics and structural equation modelling with the Smart PLS program. The results showed that network capability has positive and significant effect on marketing performance and knowledge creation, knowledge creation has positive and significant effect on product innovation, and product innovation has positive and significant effect on marketing performance